Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.29081/jesr.v27i3.282
|View full text |Cite
|
Sign up to set email alerts
|

HETEROGENEOUS CATALYSIS USING BENTONITE-SUPPORTED Fe-Co-Ni TRIMETALLIC NANOPARTICLES

Abstract: Herein, the synthesis and characterization of a bentonite-supported Fe-Co-Ni trimetallic nanocatalyst applied in transesterification reaction was reported. The synthesized heterogeneous catalyst was used to investigate the production of biodiesel by varying the reaction parameters using Box-Behnken design response surface methodology (RSM-BBD). An optimum biodiesel yield of 95.2 % was obtained at methanol to oil ratio of 10:1, reaction time of 2 hours, reaction temperature of 55  and catalyst concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…As depicted in Figure 1, the formation of glycerine tended to decrease from 31 to 18% when the proportion of bentonite used as the co-catalyst was increased from 30 to 40%. This indicated that the use of bentonite clay as a co-catalyst in the transesterification of WCO was quite valuable in cutting the excessive use of chemical catalysts (Alade et al 2021). The results showed that even if bentonite clay was used in high proportions, it still has potential to reduce the glycerine formation, and could subsequently enhance the biodiesel production during the transesterification.…”
Section: Resultsmentioning
confidence: 96%
“…As depicted in Figure 1, the formation of glycerine tended to decrease from 31 to 18% when the proportion of bentonite used as the co-catalyst was increased from 30 to 40%. This indicated that the use of bentonite clay as a co-catalyst in the transesterification of WCO was quite valuable in cutting the excessive use of chemical catalysts (Alade et al 2021). The results showed that even if bentonite clay was used in high proportions, it still has potential to reduce the glycerine formation, and could subsequently enhance the biodiesel production during the transesterification.…”
Section: Resultsmentioning
confidence: 96%